2003
DOI: 10.1080/713813428
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic sequelae in neurologically recovered obstetrical brachial plexus injury. Case study and literature review

Abstract: There is no consensus on the cause of contractures and bony deformities in children with OBPI. Conservative methods of treatment have changed over the years, without research on the outcome of these treatment changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Although this final sub-division can only be made in retrospect, the distinction between children with and without need for intensive treatment can now be made in good time. The importance of this was confirmed by the results of our previous studies, in which children with delayed complete neurological recovery were found to have a high incidence of shoulder contracture and bony deformity ter Steeg et al 2003).…”
Section: Discussionmentioning
confidence: 60%
“…Although this final sub-division can only be made in retrospect, the distinction between children with and without need for intensive treatment can now be made in good time. The importance of this was confirmed by the results of our previous studies, in which children with delayed complete neurological recovery were found to have a high incidence of shoulder contracture and bony deformity ter Steeg et al 2003).…”
Section: Discussionmentioning
confidence: 60%
“…4 Three months was selected as "satisfactory" referral timing. While evidence is not sufficient to support specific nonoperative physical therapy protocols with referral at 1 month, 10,18,63 there is growing evidence to support operative nerve repair beginning at 3 months of age. 19 Canadian OBPI surgeons indicate preference for early referral 4,7,12 to allow for serial assessment by a multidisciplinary team, with indications for nerve repair beginning at 3 months.…”
Section: Referral Processesmentioning
confidence: 99%
“…Chan (2002) describes splinting as one of the most useful modalities to minimize deformities, prevent joint contractures, and substitute loss of motor control following a peripheral nerve injury [5]. Ter Steeg et al (2003) reported that shoulder bracing for BRBPI was recommended in the first half of the twentieth century, but then advised against it, and subsequently is seldom mentioned in the modern literature [24]. Existing literature does not clarify why there was a reversal of recommendations, but these papers retrospectively comment that splinting may have led to difficult contractures in the externally rotated and abducted position.…”
Section: Differential Forearm and Humeral Rotation With Elbowmentioning
confidence: 99%
“…In children with otherwise “good” BRBPI recovery, there are very commonly impairments in the passive and active range of both supination (Sup) and shoulder external rotation (ER) [12, 13, 16, 24]. Theories of why this occurs include the following: imbalance of strength in muscles with recovering compared to non-injured nerves, relative agnosia affecting development during recovery of joint sensation and movements, direct shoulder capsular injury during birth, and imbalanced functional reinnervation of some muscles.…”
Section: Introductionmentioning
confidence: 99%